Can Medicinal Properties of Watercress be Relevant to Human Health? A Systematic Review Based on Preclinical Study In vivo - Clemente, Mirna; Miguel, Marilis Dallarmi; Felipe, Karina Bettega; Fujiwara, Gislene Mari; Fernandes, Luiz Claudio; Dias, Joseane de Fatima Gaspari; Zenin, Sandra Maria Warumby; Hirota, Beatriz Cristina Konopatzki; Miguel, Obdulio Gomes (Pharmacognosy Reviews)
Nasturtium officinale (Watercress) is a perennial dicotyledonous herbaceous plant and a member of the Brassicaceae family. The leaves of this plant are used as a home remedy as expectorant and hypoglycemic. They can also be used in the treatment of hyperlipidemia, hypertension, as well as many other chronic diseases. This finding supports the idea of watercress being a health promoter. In addition, this study intends to provide recommendations for future research. This systematic review was performed by Science Direct, MEDLINE, Cochrane, and Scopus from July 2017 to August 2018. A total of 14 preclinical studies with watercress were selected by the inclusion and exclusion criteria, 13 were with rats and mice and 1 fish. The search terms used were “bioactive compounds,” “Nasturtium,” “preclinical study,” and “systematic review.” For the quality of the individual studies, we adopted the risk of bias. The results of the selected articles with Nasturtium in animals showed positive effects on the improvement of the immune system, hypoglycemic hypercholesterolemia, and anti‑inflammatory activity, sex hormones synthesis, the preventive effect on the renal stone formation, and others. Since Nasturtium is widely used for therapeutic and nontherapeutic purposes that trigger its significant value, a new approach is necessary. Different combinations and the numerous medicinal properties of its extract juice and leaves, whether administrated orally or topically, demand further studies about other useful and unknown properties of this multipurpose plant. Finally, it is suggested by our reviewers that more studies with animals to be applied to human health, should be investigated of bioactive compounds from watercress.
Keywords: Bioactive compounds and systematic review; in vivo; Nasturtium officinale; preclinical trials; watercress